MEMBANTU PENANGANAN MASALAH KESEHATAN MASYARAKAT DENGAN INTERPROFESIONAL EDUCATION (IPE) - Hadi, Mochammad Choirul; Kusumajaya, Anak Agung Ngurah; Marhaeni, Gusti Ayu; Mustika, I Wayan; Gejir, I Nyoman; Sudiantara, Ketut; Suardana, I Wayan; Puryana, I Gusti Putu Sudita; Dewi, Ni Nyoman Astika; Habibah, Nur (Poltekkes Kemenkes Denpasar, 2023)
An integrated manner of Community Engagement Activities done by using the concept of Interprofessional Education (IPE) engages health workers and village midwives in the work area of Puskesmas Kerambitan I as the target. This activity aims to apply the IPE to improve community health status in the working area of Puskesmas Kerambitan I Tabanan Regency. In the implementation of community service activities used several methods, such as structured interview methods to explore public health problems, methods of extension for giving some health materials as well as, and methods of direct practice to the community during the day of health services. This activity successfully involves the target of training of 30 people consisting of Village Midwife and Community Health Center Staff and Health Workers from 7 villages as many as 21 people, and target of public health service as much as 98 out of 100 people invited Community Service Activity with IPE method is completed by involving all departments in Poltekkes Kemenkes Denpasar.